Sustainable Infrastructure Financing for Small Towns in China : Approaches to Attract Long-Term Capital for Small-Scale Infrastructure Projects - Campanaro, Alessandra (World Bank, Washington, DC, 2017)
China has experienced rapid urbanization in the past three decades, which has successfully brought unparalleled economic growth, employment creation and improvement in living standards. This paper is focused on exploring the feasibility of establishing a pooled Infrastructure Financing Facility (IFF) at the sub-national level to provide sustainable long-term finance to infrastructure projects in small towns. The paper reviews China’s fiscal and infrastructure financing system, including the 2014 amendment of China’s Budget Law and associated regulations, presents an overview of pooled IFFs, and explores the potential application of a pooled financing facility in China, specifically for urban infrastructure projects in the greater Shanghai region.